2001
DOI: 10.1677/joe.0.1700425
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid and vitamin D(3) powerfully inhibit in vitro leptin secretion by human adipose tissue

Abstract: Leptin, the product of the ob gene, is secreted into the circulation by white adipose tissue; its major role being to participate in the regulation of energy homeostasis. Plasma leptin levels are mainly determined by the relative adiposity of the subject; however, the great dispersion of values for any given body mass index and the noteworthy gender-based differences indicate that other factors are operating.Steroid hormones actively participate in the regulation of leptin secretion; however, non-steroid nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
80
3
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 40 publications
0
80
3
2
Order By: Relevance
“…In support of the specificity of the action observed, other pituitary hormones, such as PRL and ACTH, were devoid of action, and the same lack of direct activity was observed for pituitary hormones with similar structures to TSH, such as LH and FSH. These data supply information for understanding the variables controlling leptin levels in plasma and support the view that net adipose mass is the main determinant of these levels, but that in addition the action of steroid (Casabiell et al 1998, Piñeiro et al 1999 and non-steroid hormones (Menendez et al 2001) plus other non-hormonal factors (Piñeiro et al 1998, Peino et al 2000, determine the final level of leptin release into plasma. The organ culture model used in this work shows a considerable advantage, such as simplicity and convenience of manipulation, facts highly relevant when dealing with adipose tissue.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In support of the specificity of the action observed, other pituitary hormones, such as PRL and ACTH, were devoid of action, and the same lack of direct activity was observed for pituitary hormones with similar structures to TSH, such as LH and FSH. These data supply information for understanding the variables controlling leptin levels in plasma and support the view that net adipose mass is the main determinant of these levels, but that in addition the action of steroid (Casabiell et al 1998, Piñeiro et al 1999 and non-steroid hormones (Menendez et al 2001) plus other non-hormonal factors (Piñeiro et al 1998, Peino et al 2000, determine the final level of leptin release into plasma. The organ culture model used in this work shows a considerable advantage, such as simplicity and convenience of manipulation, facts highly relevant when dealing with adipose tissue.…”
Section: Discussionmentioning
confidence: 57%
“…However, both in experimental animals (Escobar-Morreale et al 1997, Fain et al 1997, and in humans (Corbetta et al 1997, Sreenan et al 1997, Valcavi et al 1997, Leonhardt et al 1998, Pinkney et al 1998, Yoshida et al 1998, no data have demonstrated in a definitive way that thyroid hormones may change circulating leptin levels, and the scarce leptin changes observed were explained by parallel alterations in body weight of the subjects under observation. Supporting that lack of action of thyroid hormones, studies with human adipose tissue showed no changes in leptin release when incubated with significant concentrations of thyroid hormones in vitro (Menendez et al 2001). The present report of a direct action of TSH on leptin secretion, exerted directly at the adipocyte level in human tissue, adds a new dimension to the complex relationship between the two points of the system, although it must be remembered that other factors continuously operate superimposed on the TSH actions in order to modulate the final levels of leptin in plasma.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Adipose tissue is metabolically active, producing cytokines and adipocyte-related hormones that can regulate the development of immunocytes 6,7 . Adipocytes have vitamin D receptors, and vitamin D can prevent differentiation of adipocytes and alter their secretion of proinflammatory cytokines and adipose-related hormones 8,9 .…”
mentioning
confidence: 99%
“…The role of 25(OH)D on adipokines, such as leptin and adiponectin, is also a major area of research interest. Evidence suggests that, in humans, leptin secretion is negatively (13), and adiponectin secretion is positively (14), controlled by serum 25(OH)D. Hence, it is also possible that 25(OH)D may affect the pathogenesis of diabetes, obesity, and dyslipidemia through alteration in adipokine concentrations (15,16). Serum 25(OH)D can potentially affect mechanisms related to type 2 diabetes and obesity pathophysiology by impairing b cell function leading to the development of insulin resistance (17).…”
Section: Introductionmentioning
confidence: 99%